Technological trends & software engineering education: a systematic review study - Nesterenko, O.V. (Проблеми програмування, 2022)
The quality of software engineering education is influenced by the consideration of modern industrial trends, IT trends and software development methodologies. The transition to a new level of industry - “Industry 4.0”, characterized by robotics and cyber-socialization, brings a wave of new, never-before-seen challenges to the field of IT and programming. Under such conditions, it is impossible to achieve the desired synergistic effect without the formation of an appropriate informational and educational environment in institutions of higher education. One of the sources of the content of such an environment can be the publications of the world scientific community registered in international scientometric databases. On this basis, it becomes possible not only to provide effective digital educational content, but also to choose and use the latest technological means of learning support. A targeted review of primary sources in the Web of Science Core Collection database made it possible to identify, select, synthesize and evaluate research evidence relevant to the research questions: (i) what technological trends are analyzed in research, (ii) what information technologies are considered in research, (iii) what strategies are reflected in publications to overcome the above challenges of SE teaching and learning. According to the results of the study, we offer to improve the educational and methodological support of software engineering education based on ontological modeling of the integration of the requirements of modern trends in the development of the industry and the IT sector, international recommendations and the capabilities of technological teaching aids. This approach is a good basis for the processes of intellectualization of information systems of the educational environment and the construction of appropriate technological educational tools on their basis. На якість освіти з інженерії програмного забезпечення впливає урахування в її методичному забезпеченні сучасних промислових трендів, ІТ-тенденцій та методологій розробки програмного забезпечення. Перехід до нового щабля промисловості – «Індустрії 4.0», що характеризується роботизацією і кібер-соціалізацією, несе хвилю нових, ще не бачених викликів у сферу ІТ і програмування. У таких умовах досягти потрібного синергетичного ефекту неможливо без формування у закладах вищої освіти відповідного інформаційно-освітнього середовища. Одним з джерел контенту такого середовища можуть бути публікації світової наукової спільноти, що реєструються у міжнародних наукометричних базах даних. На цій основі стає можливим не лише забезпечення ефективного цифрового освітнього контенту, а й вибір та застосування новітніх технологічних засобів підтримки навчання. Проведений цілеспрямований огляд первинних джерел у базі Web of Science Core Collection дозволив визначити, відібрати, синтезувати та оцінити докази дослідження, що мають відношення до поставлених дослідницьких питань: які технологічні тренди аналізуються у дослідженнях, які інформаційні технології розглядаються у дослідженнях, які стратегії відображені в публікаціях для подолання вище наведених проблем викладання та навчання SE. В результаті запропоновано удосконалення навчально-методичного забезпечення освіти з інженерії програмного забезпечення на основі онтологічного моделювання інтеграції вимог сучасних трендів розвитку індустрії та галузі ІТ, міжнародних рекомендацій та можливостей технологічних засобів навчання. Такий підхід є гарним підґрунтям процесів інтелектуалізації інформаційних систем освітнього середовища та побудови на їхній основі відповідних технологічних навчальних засобів.